Influence of soil type on damping reduction factor: A stochastic analysis based on peak theory - Greco, Rita; Fiore, Alessandra; Briseghella, Bruno (Soil dynamics and earthquake engineering (1984), 2018)
Damping reduction factor plays a central role both in scientific literature and seismic codes, but still now proposed formulations show a quite large scatter. The main goal of the present work is to explore a new definition of the damping reduction factor. The concept of stochastic response spectrum is adopted in order to predict the earthquake response of a linear SDoF system, on the basis of the random vibration theory for non-stationary process. The peak of the response of a SDoF system under a non-stationary stochastic process is used to define the stochastic displacement spectrum. The damping reduction factor is thus evaluated as the ratio between the maximum displacement of systems with a given damping and a conventional one subject to the same earthquake. •Damping reduction factors plays a central role both in scientific literature and seismic codes, but still now proposed formulations show a quite large scatter.•The concept of stochastic response spectrum is used for predicting the earthquake response of a structural system by adopting the random vibration theory for non-stationary processes.•The peak of the response of a SDoF system under a non-stationary stochastic process is used to define the stochastic displacement spectrum.